Publications in the Armenian Press about the Turkish-Armenian Border Clashes (May-September 1920) - Minasyan, Edik; Mkhoyan, Hayk (History and Culture, 2022)
Preparing for a campaign against Armenia, M. Kemal and K. Karabekir, in May-September 1920, organized riots and clashes in the border regions of Armenia: Kars, Sarighamish, Zangibasar, Vedibasar, Olti, Surmalu. They were also largely using the human resources of Azerbaijan. The Turkish-Tatars (Caucasian Tatars), receiving funds from the Turkish central authorities, invaded Armenian settlements, destroyed, looted and killed the local Armenian residents. In order to put an end to this situation, in the summer of 1920, the Armenian military command set out to clear a number of territories from the Turks. These events were widely covered in a number of organs of the Armenian press, among which were “Mshak”, “Yaraj”, “Zhoghovrdi Dzayn”, “Zhoghovurd” and others. Other organs mainly published the publications of these periodicals. The material presented in them shows the motives and course of the border clashes, and also provides some statistical information about the victims, wounded, as well as the ratio of forces. These publications of the Armenian press became the basis of our research. In the article, we also referred to the foreign political realities of those months, which in many cases caused border movements and clashes, as a result of which a war against RA was unleashed in 1920, which was devastating for the Armenian people, because the Armenians were deprived of a huge part of their historical motherland.